Pre-marital education (PME) program for marriage readiness and stunting prevention to women of childbearing age - Leila Nisya Ayuanda; Nur Intan Kusuma; Amin Aji Budiman (Malahayati International Journal of Nursing and Health Science, 2024)
Background: Indonesia is one of the countries with a high burden of malnutrition, including stunting. One preventive measure for stunting is the optimization of pre-pregnancy services (preconception). Preconception services, especially for prospective brides and grooms, aim to identify and modify biomedical, psychological, and social risks related to women's health and pregnancy conditions through an optimal early detection strategy. Current issues regarding stunting can indeed be prevented through optimal pregnancy and marriage planning. Therefore, a strategy is needed to develop comprehensive pre-marriage planning through premarital classes.Purpose: To determine the effectiveness of pre-marital education (PME) program for marriage readiness and stunting prevention to women of childbearing ageMethod: This research used a quantitative research design with a quasi-experimental one-group pretest-posttest approach. The instrument used a questionnaire on the physical, psychological, and social readiness of premarital individuals that had been tested for validity and reliability. The sampling method used accidental sampling, and 49 prospective brides and grooms were obtained as participants.Results: The results indicated that the "Paketin Canting" class titled "Paket Kelas Catin Cegah Stunting" had an effect on the biopsychosocial readiness of premarital individuals. In future research, the Catin class method can be further developed to enhance motivation and utilization. Additionally, further research is needed on the impact of Catin classes on reducing stunting rates in Indonesia, and statistical tests show a significant difference before and after the Paketin Canting intervention on the biopsychosocial readiness of premarital individuals (p-value = 0.000).Conclusion: There is an effect of the "Paketin Canting"- a pre-marital education program on the physical, psychological, and social readiness of premarital individuals.